PERANAN SEKRETARIAT DEWAN DALAM PELAKSANAAN FUNGSI ANGGARAN DEWAN PERWAKILAN RAKYAT DAERAH - Weddy Suhandani (Universitas Borneo Tarakan, 2025)
This research analyzes the role of the Secretariat of the Regional House of Representatives (DPRD) in supporting the implementation of the budgeting function within regional government. The Secretariat of the DPRD serves as an administrative and technical support unit that facilitates budgeting activities, including planning, implementation, reporting, accountability, and financial supervision. This study employs a normative legal research method supported by empirical data through the examination of relevant laws and regulations on regional governance and financial management. The findings indicate that the Secretariat of the DPRD has generally carried out its role effectively in accordance with applicable regulations and as an integral part of the Regional Revenue and Expenditure Budget system. However, several challenges remain, particularly related to human resource competence and procedural delays in financial accountability reporting. Therefore, continuous improvement is needed to strengthen professionalism, accountability, and effective financial governance.